The Role of Vitamin D and Vitamin D Receptor in Immunity to Leishmania major Infection - James P. Whitcomb; Mary DeAgostino; Mark Ballentine; Jun Fu; Martin Tenniswood; JoEllen Welsh; Margherita Cantorna; Mary Ann McDowell (Journal of Parasitology Research)
Vitamin D signaling modulates a variety of immune responses. Here, we assessed the role of vitamin D in immunity to experimental leishmaniasis infection in vitamin D receptor-deficient mice (VDRKO). We observed that VDRKO mice on a genetically resistant background have decreased Leishmania major-induced lesion development compared to wild-type (WT) mice; additionally, parasite loads in infected dermis were significantly lower at the height of infection. Enzymatic depletion of the active form of vitamin D mimics the ablation of VDR resulting in an increased resistance to L. major. Conversely, VDRKO or vitamin D-deficient mice on the susceptible Th2-biased background had no change in susceptibility. These studies indicate vitamin D deficiency, either through the ablation of VDR or elimination of its ligand, 1,25D3, leads to an increase resistance to L. major infection but only in a host that is predisposed for Th-1 immune responses.